2020
DOI: 10.1007/s40200-020-00675-1
|View full text |Cite
|
Sign up to set email alerts
|

Association of plasminogen activator inhibitor-1 4G5G Polymorphism with risk of diabetic nephropathy and retinopathy: a systematic review and meta-analysis

Abstract: Background The 4G5G polymorphism of Plasminogen activator inhibitor-1 (PAI-1) gene is reported to be associated with diabetes nephropathy and retinopathy (DNR) risk. However, the findings are conflicting. Herein, we conducted a case-control and meta-analysis study to explore the association of PAI-1 4G5G polymorphism with risk of DNR. Methods We retrieved PubMed, EMBASE, Web of Knowledge, and CNKI databases and screened eligible studies up to August 15, 2020. The strength of associations was assessed by odd ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 49 publications
0
7
1
Order By: Relevance
“…In contrast to our findings, Dastgheib et al (2020) found that the PAI-1 4G5G polymorphism was associated with increased risk of DN and diabetic retinopathy (DR) risk [ 34 ]. Furthermore, Wong et al (2000) concluded that SERPINE1 4G/4G is an independent factor for the development of DN in Chinese patients with T2DM and also exhibits a synergistic effect with the allele D of ACE gene on development of DN [ 27 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to our findings, Dastgheib et al (2020) found that the PAI-1 4G5G polymorphism was associated with increased risk of DN and diabetic retinopathy (DR) risk [ 34 ]. Furthermore, Wong et al (2000) concluded that SERPINE1 4G/4G is an independent factor for the development of DN in Chinese patients with T2DM and also exhibits a synergistic effect with the allele D of ACE gene on development of DN [ 27 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Among the numerous genetic loci studied in both individual studies [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ] and meta-analyses [ 32 , 33 , 34 ] is serpin family E member 1 ( SERPINE1 ) gene, also known as Plasminogen activator inhibitor-1 (PAI-1), which is a member of the serine proteinase inhibitor (serpin) superfamily and constitutes the principal inhibitor of tissue plasminogen activator (tPA) and urokinase (uPA) leading to inhibition of fibrinolysis [ 32 ]. The SERPINE1 gene is located at chromosome band 7q22.1.…”
Section: Introductionmentioning
confidence: 99%
“…Our combined data based on ten studies with 11,755 infected cases and 942 deaths showed that the [21,48,49]. It is well known that allcause mortality rate in patients with DM is higher than in patients without DM [50][51][52]. Our pooled data showed that the proportion of SARS-COV-2 infection in the Iranian patients with DM was 16.3 %.…”
Section: Discussionmentioning
confidence: 68%
“…A number of previous studies reported a bidirectional relationship between SARS-CoV-2 and the onset of diabetes [3]. Although diabetes is prevalent worldwide, healthcare professionals are worried about this new pandemic's consequences regarding diabetes [4]. While it has been shown that persons with diabetes (PWD) are considered as high risk population for developing complications [5]; herein, we presented a young patient with new onset diabetes after SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 91%